2015
DOI: 10.1530/jme-15-0226
|View full text |Cite
|
Sign up to set email alerts
|

Maternal high-fat diet influences stroke outcome in adult rat offspring

Abstract: Diet-induced epigenetic modifications in early life could contribute to later health problem. However, it remains to be established whether high-fat diet (HFD) consumption during pregnancy and the suckling period could predispose the offspring to stroke. The present study investigated the influence of maternal HFD on stroke outcome in adult offspring. Female Sprague-Dawley rats were fed a normal diet (5.3% fat) or a HFD (25.7% fat), just before pregnancy until the end of lactation. Male offspring were fed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
2
7
0
1
Order By: Relevance
“…Using the same model and markers, the present study explores whether the co-existence of maternal HFD, known to induce an amplified response to acute stress, could act as an aggravating factor in PA. Data obtained have shown an intensified hippocampal neuroinflammation and injury in the HF-PA group when compared to the PA group, supporting a cumulative effect of maternal HFD on the extent of PA-induced hippocampal damage. Our findings are in accordance with Lin et al [15], who reported that HFD during pregnancy might worsen the post-ischemic outcome. This finding can be correlated with the long-lasting presence of low-levels of proinflammatory mediators induced by the maternal diet, which can be transmitted in utero to the fetus [16].…”
Section: Discussionsupporting
confidence: 94%
“…Using the same model and markers, the present study explores whether the co-existence of maternal HFD, known to induce an amplified response to acute stress, could act as an aggravating factor in PA. Data obtained have shown an intensified hippocampal neuroinflammation and injury in the HF-PA group when compared to the PA group, supporting a cumulative effect of maternal HFD on the extent of PA-induced hippocampal damage. Our findings are in accordance with Lin et al [15], who reported that HFD during pregnancy might worsen the post-ischemic outcome. This finding can be correlated with the long-lasting presence of low-levels of proinflammatory mediators induced by the maternal diet, which can be transmitted in utero to the fetus [16].…”
Section: Discussionsupporting
confidence: 94%
“…[2][3][4] Consistently, maternal HFD intake also renders the brain more susceptible to the consequences of ischemic injury in adult offspring. 5 The present study expands the result by demonstrating that maternal HFD consumption would substantially influence adult offspring cerebrovascular health, providing an important mechanism for maternal HFD-induced aggravated stroke outcome. Moreover, because of the cerebral circulation remodeling, maternal HFD exposure would also give rise to an offspring phenotype predisposed to the development of stroke and other cerebrovascular diseases in adulthood.…”
Section: Discussionsupporting
confidence: 74%
“…Baseline cerebrovascular ET-1 levels were also measured in the MCA homogenate, using the immunoassay kits. Subset of rats were applied with temporary middle cerebral artery occlusion (MCAO), 5 and post-stroke plasma ET-1 levels were determined 2 h later. In brief, a silicon-coated 5-0 nylon monofilament (tip diameter: 0.31 AE 0.02 mm) was introduced into the external carotid artery and advanced up the internal carotid artery to the Circle of Willis (18-19 mm from the carotid bifurcation), where it blocked the origin of the MCA to decrease blood flow for 1.5 h. Cerebral blood flow reduction of at least 80% of baseline was confirmed as ischemic attack by Laser Doppler Flowmetry (Moor Instruments, UK).…”
Section: Metabolic Parameters and Et-1 Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed above, whether this is due to post-natal adaptations during brain maturation or insensitivity of the current methods to detect small or selective changes in BBB permeability remains unknown. Endothelial denudation and thickening of the middle cerebral artery has been reported in 6-month old rat offspring of obese mothers (Lin et al, 2018) and neonatal and adult HF/C offspring display larger infarct volumes and poorer functional deficits after stroke compared to C/C rats (Lin et al, 2016; Teo et al, 2017). We have previously reported that vessel morphology and thickness and GFAP expression were altered in the hippocampus of 5-month old HF/C male mice compared to C/C offspring (Hawkes et al, 2015).…”
Section: Discussionmentioning
confidence: 99%